2011
DOI: 10.1001/jama.2011.1364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increasing Doses of Saw Palmetto Extract on Lower Urinary Tract Symptoms

Abstract: Context Saw palmetto fruit extracts are widely used for treating lower urinary tract symptoms attributed to benign prostatic hyperplasia. However, recent clinical trials have questioned their efficacy, at least at standard doses (320 mg daily). Objective To determine the effect of a saw palmetto extract at up to three times the standard dose on lower urinary tract symptoms attributed to benign prostatic hyperplasia. Design Multicenter placebo-controlled randomized trial conducted from June, 2008 through Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
2
26

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(155 citation statements)
references
References 30 publications
3
124
2
26
Order By: Relevance
“…Barry et al 36 conducted an RCT of 369 men with nocturia who were treated with saw palmetto or placebo. No difference in nocturia outcomes was seen at 24-or 48-week follow-up (LOE 2).…”
Section: Phytotherapymentioning
confidence: 99%
“…Barry et al 36 conducted an RCT of 369 men with nocturia who were treated with saw palmetto or placebo. No difference in nocturia outcomes was seen at 24-or 48-week follow-up (LOE 2).…”
Section: Phytotherapymentioning
confidence: 99%
“…EAU guidelines state that this herbal extracts significantly reduce nocturia in comparison with placebo [17]. On the contrary, some authors described that Serenoa repens extracts have not shown more effectiveness than placebo in the treatment of BPH [24][25][26]. However, more recent data favor the use of Serenoa repens extracts in milder BPH cases with promising results [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, a placebo‐controlled study of 369 men has demonstrated no differences in reduction of LUTs between Saw Palmetto and placebo 122.…”
Section: Other Treatmentsmentioning
confidence: 98%